Parkinson's disease patients' needs during the COVID‐19 pandemic in a red zone: A framework analysis of open‐ended survey questions. (6th February 2021) - Cavallieri, Francesco; Sireci, Francesca; Fioravanti, Valentina; Toschi, Giulia; Rispoli, Vittorio; Antonelli, Francesca; Costantini, Massimo; Ghirotto, Luca; Valzania, Franco
Abstract: Background and purpose: During the first phase of the COVID‐19 pandemic, a lockdown was imposed in Italy. The aim of this study was to investigate the perceptions, feelings and unmet needs of Parkinson's disease (PD) patients who experienced the 2‐month lockdown in a "red zone" in the northern part of Italy during the COVID‐19 outbreak. Methods: The study had a descriptive design that used a cross‐sectional online survey which included open‐ended questions to elicit responses on the participant's feelings concerning their risk of contracting coronavirus, how their physical activity had changed, and their personal needs, dictated by their condition, which were not met in this pandemic period as compared to previous periods. Demographic data were analysed using descriptive frequencies, while the open‐ended questions were analysed using thematic framework analysis. Results: The study included 103 participants (63 men/40 women [61.17 vs. 38.83%]). Framework analysis led to the identification of four main themes: (i) fearing the risk of contracting coronavirus; (ii) reduction of physical activity; (iii) perception of the risk of not being able to access outpatient clinics or support services; and (iv) negative experiences of the important reduction in socialization. The perceptions of unmet needs appeared to be greater than the actual experience, particularly for the reduction in physical activity and the interruption of contacts with the neurologist and other specialists. Conclusions: This study highlights how perceptions and actual experience shape the meaning of living with PD during the pandemic. Worth noting is the divergence between perceptions and real impact in some aspects of the COVID‐19 outbreak. Abstract : Parkinson's disease patients' needs during the COVID‐19 pandemic in a red zone: A framework analysis of open‐ended survey questions Francesco Cavallieri, Francesca Sireci, Valentina Fioravanti, Giulia Toschi, Vittorio Rispoli, Francesca Antonelli, Massimo Costantini, Luca Ghirotto*, Franco Valzania. The authors investigated the perceptions, feelings and unmet needs of Parkinson's Disease patients who experienced a two‐month lockdown in a "red zone" during the COVID‐19 outbreak. A cross‐section online survey was performed; framework analysis of the open‐ended questions identified four main themes: fearing the risk of contracting coronavirus; the reduction of physical activity; the perception of the risk of not being able to access outpatient clinics or support services and the suffering from the important reduction in socialization.